2022
DOI: 10.1186/s13075-022-02851-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of response to methotrexate in patients with rheumatoid arthritis: a machine learning approach using clinical trial data

Abstract: Background Methotrexate is the preferred initial disease-modifying antirheumatic drug (DMARD) for rheumatoid arthritis (RA). However, clinically useful tools for individualized prediction of response to methotrexate treatment in patients with RA are lacking. We aimed to identify clinical predictors of response to methotrexate in patients with rheumatoid arthritis (RA) using machine learning methods. Methods Randomized clinical trials (RCT) of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 43 publications
0
10
0
2
Order By: Relevance
“…In rheumatology, recent initiatives used genetic data and machine learning to predict response to MTX [10][11][12]. However, implementing these models in clinical practice remains a challenge because genetic data are unavailable in usual practice.…”
Section: Rheumatology Key Messagesmentioning
confidence: 99%
“…In rheumatology, recent initiatives used genetic data and machine learning to predict response to MTX [10][11][12]. However, implementing these models in clinical practice remains a challenge because genetic data are unavailable in usual practice.…”
Section: Rheumatology Key Messagesmentioning
confidence: 99%
“…Yet, it still seems not possible to predict the outcomes of patients on methotrexate based on biomarkers or genetic investigations. A retrospective analysis of clinical predictors of methotrexate response conducted by Duong et al showed that baseline disease activity score-28-eryhtrocyte sedimentation rate (DAS28-ESR), positive ACPA, and health assessment questionnare (HAQ) score were the predictors for drug response [36]. Our study demonstrated that only higher DAS 28 score is the predictor for remission in the methotrexate therapy both in LORA and YORA patients.…”
Section: Dıscussıonmentioning
confidence: 46%
“…Thus, they do not seem to improve prediction of therapeutic response [ 41 ]. However, machine learning methods that utilize approaches such as the least absolute shrinkage and selection operator and random forests methods may identify new previously unrecognized predictors of disease severity and response to a therapy [ 42 ]. Clinicians and clinical trial experts in each specialty should contemplate using these “big data” to create expanded risk models that include more than the obvious risk factors.…”
Section: Rethinking Study Designmentioning
confidence: 99%